2015
DOI: 10.1186/s12864-015-1283-0
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomic analysis of hepatic responses to testosterone deficiency in miniature pigs fed a high-cholesterol diet

Abstract: BackgroundRecent studies have indicated that low serum testosterone levels are associated with increased risk of developing hepatic steatosis; however, the mechanisms mediating this phenomenon have not been fully elucidated. To gain insight into the role of testosterone in modulating hepatic steatosis, we investigated the effects of testosterone on the development of hepatic steatosis in pigs fed a high-fat and high-cholesterol (HFC) diet and profiled hepatic gene expression by RNA-Seq in HFC-fed intact male p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 95 publications
(137 reference statements)
2
30
2
1
Order By: Relevance
“…In the previous study, APOE, APOC3, and APOA5 were shown to be positively associated with plasma triglyceride levels [31,32], which indicated VAT accumulation. Accordingly, our previous results found the levels of serum triglyceride were highly significant increased under testosterone deficiency in pigs fed a HFC diet [18]. Thus, our data suggested that these enhanced lipoproteins might contribute to VAT changes caused by testosterone deficiency under HFC feeding.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the previous study, APOE, APOC3, and APOA5 were shown to be positively associated with plasma triglyceride levels [31,32], which indicated VAT accumulation. Accordingly, our previous results found the levels of serum triglyceride were highly significant increased under testosterone deficiency in pigs fed a HFC diet [18]. Thus, our data suggested that these enhanced lipoproteins might contribute to VAT changes caused by testosterone deficiency under HFC feeding.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, by using pig model, our previous study discovered that castration-induced testosterone deficiency resulted in significant changes of miRNAs in subcutaneous adipose tissue, which were associated with fatty acid metabolism by acting on their target genes [17]. Moreover, we also found that testosterone deficiency caused severe hypercholesterolemia and hepatic steatosis in pigs fed a HFC diet and could be reversed by testosterone replacement therapy [18,19]. However, thus far, little is known about the underlying mechanisms of changes in VAT induced by testosterone deficiency under HFC diet, particularly in alterations of gene expression and regulation in VAT caused by testosterone changes.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Liver tissues were collected from the following three groups: high fat diet-fed intact male pigs, castrated male pigs, and castrated male pigs with testosterone replacement, from which total RNA was extracted and sequenced in 100-bp paired-end reads (SRP049250)44.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome sequencing is used to study transcripts of particular tissues or organs of a species in a particular state and is superior to microarrays in terms of information volume and accuracy [ 12 ]. By constructing a transcriptome library, we can obtain information about transcripts and alternative splicing and can determine the differential expression patterns of specific genes [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%